2016
DOI: 10.1002/hipo.22558
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of CB2 cannabinoid receptors reduces synaptic transmission and long‐term potentiation in the mouse hippocampus

Abstract: The effects of cannabinoids are mostly mediated by two types of cannabinoid receptors--CB1 receptors in the nervous system and CB2 receptors in the immune system. However, CB2 cannabinoid receptors have recently been discovered in the brain and also implicated in neurophysiological functions. The deletion of CB2 receptors in mice induces long-term memory deficits and schizophrenia-like behaviors, implying that endogenous activity of CB2 receptors might be involved in neuropsychiatric effects. Little is known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 40 publications
6
44
0
1
Order By: Relevance
“…Using a similar preparation, the same research group (Kim and Li, 2015) has demonstrated that chronic CB 2 receptor agonism elevates the frequency of quantal glutamate release in CA1, which does not occur in slices from schizophrenia-like CB 2 knockout mice. Slices from the same transgenic mice have also been reported to undergo weaker LTP in CA1 (Li and Kim, 2016; Figure 3D). Therefore, the hippocampus itself is prone to alterations in the mGluR/eCB interplay, which could contribute to downstream dysfunctions in mPFC, VTA, and other schizophrenia-relevant brain sites.…”
Section: The Ecb System In Schizophrenia: Electrophysiological Findinmentioning
confidence: 74%
See 2 more Smart Citations
“…Using a similar preparation, the same research group (Kim and Li, 2015) has demonstrated that chronic CB 2 receptor agonism elevates the frequency of quantal glutamate release in CA1, which does not occur in slices from schizophrenia-like CB 2 knockout mice. Slices from the same transgenic mice have also been reported to undergo weaker LTP in CA1 (Li and Kim, 2016; Figure 3D). Therefore, the hippocampus itself is prone to alterations in the mGluR/eCB interplay, which could contribute to downstream dysfunctions in mPFC, VTA, and other schizophrenia-relevant brain sites.…”
Section: The Ecb System In Schizophrenia: Electrophysiological Findinmentioning
confidence: 74%
“…(C) In vitro assessment of mPFC synaptic plasticity and glutamatergic neurotransmission after adolescent WIN or early-life PCP exposure: association with schizophrenia-like symptoms (Lafourcade et al, 2007; Jew et al, 2013; Lovelace et al, 2014, 2015). (D) In vitro assessment of CA1 synaptic plasticity and eCB neurotransmission: relationships with schizophrenia risk factors and cannabinoid receptor activation (Du et al, 2013; Kim and Li, 2015; Li and Kim, 2016). 2-AG, 2-arachidonoyl-glycerol; adolesc, adolescent; antag, antagonism; dent, dentate; eCB-LTD, endocannabinoid long-term depression; ent, entorhinal; γ, gamma oscillations; hyperlocom, hyperlocomotion; KO, knockout; L, layer; LTP, long-term potentiation; meth, methamphetamine; mGluR, metabotropic glutamate receptors; mPFC, medial prefrontal cortex; NAc, nucleus accumbens; PCP, phencyclidine; relev, relevant; SCZ, schizophrenia; θ, theta oscillations; vHipp, ventral hippocampus; WIN, WIN 55,212-2.…”
Section: The Ecb System In Schizophrenia: Electrophysiological Findinmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the role of CB1 receptors in the regulation of neurophysiological functions has been extensively characterized, the presence of CB2 receptors in the brain is a novel finding, and their functional significance remain to be clarified. Electrophysiological and morphological studies strongly suggest that CB2 receptors are involved in synaptic transmission and plasticity (Li and Kim, 2016). Consequently, it has been demonstrated that CB2 receptors also modulate neurophysiological functions and behaviors such as anxiety (Garcia-Gutierrez et al, 2012), impulsive behaviors (Navarrete et al, 2012), vomiting (Van Sickle et al, 2005), and pain (Jhaveri et al, 2007; Anand et al, 2009; Han et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, CB2 receptors have been thought to be exclusively expressed in the cells of the immune system (Munro et al, 1993). Despite their expression in neurons is still controversial, growing evidence strongly suggests that CB2 receptors are also expressed in the brain, and that they are involved in several neurobiological functions (Gong et al, 2006; Onaivi et al, 2006; Brusco et al, 2008; Garcia-Gutierrez et al, 2012; Navarrete et al, 2012; Li and Kim, 2016). Noteworthy, endocannabinoids, and their analogs, show binding affinity for other receptor families beyond the cannabinoid receptors, including the peroxisome proliferator-activated receptors (PPARs) (Fu et al, 2003; Bouaboula et al, 2005; O’Sullivan, 2007; Campolongo et al, 2009a; Luchicchi et al, 2010), and the transient receptor potential channels, especially vanilloid receptors transient receptor potential cation channel subfamily V member 1 (TRPV1) (Zygmunt et al, 1999; Di Marzo and De Petrocellis, 2010).…”
Section: Introductionmentioning
confidence: 99%